To solve the equation \((x−7)(x+9)=0\), we can find the solutions by setting each factor equal to zero:
- \(x - 7 = 0\) ⇒ \(x = 7\)
- \(x + 9 = 0\) ⇒ \(x = -9\)
So the solutions to the original equation are \(x = 7\) and \(x = -9\).
Now, we need to determine which of the given equations has the same solutions:
-
\(x^2 = -2x + 63\)
Rearranging gives:
\(x^2 + 2x - 63 = 0\)
Factoring gives:
\((x - 7)(x + 9) = 0\) (This has the same solutions: \(x = 7\), \(x = -9\)) -
\(x^2 = 2x - 63\)
Rearranging gives:
\(x^2 - 2x + 63 = 0\)
We can check for solutions, but it does not equal the original factors. -
\(x^2 + 2x = -63\)
Rearranging gives:
\(x^2 + 2x + 63 = 0\)
This is not factorable with real solutions, so it is not the same. -
\(x^2 - 2x - 63 = 0\)
Factoring gives:
\((x - 9)(x + 7) = 0\) (This has different solutions: \(x = 9\) and \(x = -7\))
Thus, the correct choice that matches the original equation \((x−7)(x+9)=0\) is:
\(x^2 = -2x + 63\).